Prioritize among climate-smart agricultural options and benefits for greater impact - Lamanna, Christine; Mwongera, Caroline; Läderach, Peter R.D.; Acosta, Mariola; Ampaire, Edidah L.; Eitzinger, Anton; Mwungu, Chris Miyinzi; Shikuku, Kelvin Mashisia; Winowiecki, Leigh Ann (International Center for Tropical Agriculture, 2017)
Clearly showing the benefits of certain climate-smart agricultural (CSA) interventions over others in a particular context is key to facilitating prudent investment of scarce resources.